2013
DOI: 10.1089/omi.2013.0043
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Proteome Analysis ofLeptospira interrogansserovar Lai

Abstract: Leptospirosis is one of the most important zoonoses. Leptospira interrogans serovar Lai is a pathogenic spirochete that is responsible for leptospirosis. Extracellular proteins play an important role in the pathogenicity of this bacterium. In this study, L. interrogans serovar Lai was grown in protein-free medium; the supernatant was collected and subsequently analyzed as the extracellular proteome. A total of 66 proteins with more than two unique peptides were detected by MS/MS, and 33 of these were predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 54 publications
2
22
2
Order By: Relevance
“…The methodology used in the present study identified 325 exoproteins (the L. interrogans genome encodes ϳ4,000 putative proteins), which is nearly 5-fold higher than the 66 proteins reported in a previous study (20). We propose two explanations for the observed difference in the number of proteins detected: first, protein precipitation, which was performed in the previous study and which can result in protein loss due to inefficient precipitation and resolubilization, was omitted in the present study.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The methodology used in the present study identified 325 exoproteins (the L. interrogans genome encodes ϳ4,000 putative proteins), which is nearly 5-fold higher than the 66 proteins reported in a previous study (20). We propose two explanations for the observed difference in the number of proteins detected: first, protein precipitation, which was performed in the previous study and which can result in protein loss due to inefficient precipitation and resolubilization, was omitted in the present study.…”
Section: Discussioncontrasting
confidence: 60%
“…Proteins delivered to the extracellular space likely serve essential functions for the pathogenic and saprophytic lifestyles of Leptospira spp. Previous studies focusing on extracellular proteins identified Leptospira interrogans proteins in culture supernatants (20), while another study used a bioinformatics-based approach to identify potential outer membrane and extracellular proteins (21). It has also been demonstrated that culture supernatants of L. interrogans contain proteases which can interfere with the host complement defense against Leptospira spp.…”
mentioning
confidence: 99%
“…Figure 1 depicts the distribution of T2S within the evolutionary tree of the Proteobacteria. Looking beyond the Proteobacteria, there are interesting examples of organisms that have a smaller number of T2S-related genes; e.g., Leptospira interrogans of the Spirochaetes encodes T2S CDEFGJKLMO, Chlamydia and Chlamydophila species within the Chlamydiae harbor genes for T2S CDEFG, Rhodopirellula baltica belonging to the Planctomycetes may encode T2S DEFGIKO, Aquifex aeolicus of the Aquificae carries homologs for T2S DEFGO, and Thermotoga maritima of the Thermotogae appears to encode T2S DEFG (10,(19)(20)(21)(22). In the case of Chlamydia trachomatis, one of these genes has been linked to protein secretion (20), suggesting that there may be different subclasses of T2S that deviate from the canonical system present in the Proteobacteria.…”
mentioning
confidence: 99%
“…In these situations, the triggered SOS response is not only involved in DNA repair, but also influences antimicrobial resistance spread, general stress response and induction of virulence factors in organisms as uropathogenic E. coli, Salmonella enterica and Vibrio cholerae [10,49,50]. These mechanisms probably also occur in L. interrogans, and the full characterization of the DNA damage response is the first step to identify them.…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al [49] identified one of the ssb orthologous (LA1676) as component of the extracellular proteome, opening the possibility for a new function for SSB protein in leptospira physiology.…”
Section: Homologous Recombination (Hr)mentioning
confidence: 99%